Pengaruh Literasi Keuangan dan Kesejahteraan Keuangan terhadap Perilaku Keuangan dengan Generasi sebagai Variabel Moderasi pada Generasi Muda di Semarang - Gregoria Shandra Batista; Stephana Dyah Ayu (Universitas Batanghari Jambi, 2023)
This study aims to identify factors that influence financial literacy and financial well-being on financial behavior with generation as a moderating variable for young generation in Semarang. The research method used is quantitative with data analysis techniques to test hypotheses using the SPSS 26 version technique. Data collection was by distributing questionnaires via google form and hardcopy. The samples obtained for this study amounted to 184 respondents who met the specified criteria. The results of this study indicate that financial well-being has a positive and significant influence on financial behavior. This study also proves that generational grouping has a moderating effect on financial behavior.